The Concept of Ruqyah in Islam and Exorcism in Catholicism - Syamsul Hadi Untung; Abdul Muiz (Journal of Comparative Study of Religions (JCSR), 2020)
Ruqyah is commonly understood merely as an Islamic ritual used to expel demons or jinn that disturb the body of Muslims similar to Exorcism in Catholicism. However, there are a lot of things related to both which are inappropriately known and caused misunderstandings ended with shirk. This article will discuss the concept of ruqyah in Islam comparatively with exorcism in Catholicism, as ruqyah is not only a religious ritual used to repel demons or jinn but also a form of Islamic medicine inherited from the Prophet Muhammad. Ruqyah is also classified as the Thibbun Nabawi, making it considered as a part of Sunnah. As such, Exorcism is the teachings of Jesus to the 12 Apostles. Ruqyah is done using Qur’anic verses by every Muslim, as it can be an option for Muslims in dealing with disasters in the form of pain either physical or meta-physical injury derived from the interference of Satan or Jinn. While in Exorcism, the practice can only be done by a few who have obtained the legality of the local bishop, so that the authenticity of this practice can be justified. Even so, there are still many ordinary Muslims and Catholics who do not know and even look for other solutions to the problem and even do shirk.